1995
DOI: 10.1017/s0022215100129421
|View full text |Cite
|
Sign up to set email alerts
|

CO2-laser therapy for carcinoma of the larynx

Abstract: A retrospective study was undertaken to assess the outcome of 19 consecutive patients, who underwent endolaryngeal resection with a CO2-laser for laryngeal carcinomas. Sixteen of these patients had recurrences after primary curative radiotherapy. Seventeen of the patients had a curative operation carried out. So far, four CO2-laser treatment failures have been observed (median observation time 35 months). None of the patients needed tracheostomy in connection with the operation. Voice quality was in all cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 8 publications
2
34
1
Order By: Relevance
“…Outzen and Illum 16 reported similar results. After salvage procedures, a 5-year cure-rate of 98% was achieved.…”
Section: Discussionmentioning
confidence: 52%
“…Outzen and Illum 16 reported similar results. After salvage procedures, a 5-year cure-rate of 98% was achieved.…”
Section: Discussionmentioning
confidence: 52%
“…The series of Puxeddu et al [15] is a two-center retrospective case series, with results of one included center updated in a later publication by Piazza et al [16], which, in turn, was updated by Del Bon et al [17]. Most authors reported on series of rT1 to rT2 glottic cancer, while some authors also included more advanced glottic cases (rT3 or even rT4) [11••, 1821] or supraglottic recurrences [14, 18, 2022]. …”
Section: Resultsmentioning
confidence: 99%
“…Prior investigations have found that endoscopic carbon dioxide (CO2) laser and transcervical open partial laryngectomy procedures are a reasonable strategy in selected cases, providing similar survival rates for patients who otherwise would have total laryngectomy. 2,[5][6][7][8][9][10][11][12][13][14] This is the first report to describe use of the angiolytic 532-nm KTP laser in a salvage strategy for recurrent glottic carcinoma after radiotherapy, as opposed to the typical choice of a CO2 laser. Motamed et al 2 reviewed all Medline database articles from 1985 to 2005 on salvage conservation laryngeal surgery that had a sample size of greater than 10 and a follow-up of greater than 24 months.…”
Section: Resultsmentioning
confidence: 99%